Product Market Competition and Industry Returns - Bustamante, M. Cecilia; Donangelo, Andres (Review of Financial Studies, 2017)
This paper shows that product market competition has two opposing effects on asset returns. The first relates to the pro-cyclical nature of the value destruction from expansion of competitors, which lowers exposure to systematic risk in more competitive industries. The second is related to the narrower profit margins due to competition, which increase exposure to systematic risk. We find that the first effect dominates the second, so that firms in more competitive industries generally earn lower asset returns. Our results are robust to using five alternative measures of competition and to controlling for the sample selection bias of publicly-listed firms.